Produção de sarapó (Gymnotus carapo) (Pisces: Gymnotidae) em cativeiro - Rodrigues de Souza, José; de Andrade , Dálcio Ricardo (Revista Ceres, 2025)
From January until April, 1983, a study was made at the Hydrobiological and Fisheries Management Station at the Federal University of Viçosa on the effects of fertilization on the production and development of Gymnotus carapo.